International handbook of migration, minorities and education : Understanding cultural and social differences in processes of learning - Geisen, Thomas; Bekerman, Zvi (Springer Netherlands, 2012)
Migrants and minorities are always at risk of being caught in essentialized cultural definitions and being denied the right to express their cultural preferences because they are perceived as threats to social cohesion. Migrants and minorities respond to these difficulties in multiple ways - as active agents in the pedagogical, political, social, and scientific processes that position them in this or that cultural sphere. On the one hand, they reject ascribed cultural attributes while striving towards integration in a variety of social spheres, e.g. school and workplace, in order to achieve social mobility. On the other hand, they articulate demands for cultural self-determination. This discursive duality is met with suspicion by the majority culture. For societies with high levels of migration or with substantial minority cultures, questions related to the meaning of cultural heterogeneity and the social and cultural limits of learning and communication (e.g. migration education or critical multiculturalism) are very important. It is precisely here where the chances for new beginnings and new trials become of great importance for educational theorizing, which urgently needs to find answers to current questions about individual freedom, community/cultural affiliations, and social and democratic cohesion. Answers to these questions must account for both 'political' and 'learning' perspectives at the macro, mezzo, and micro contextual levels. The contributions of this edited volume enhance the knowledge in the field of migrant/minority education, with a special emphasis on the meaning of culture and social learning for educational processes.